Managing corneal disease: focus on suppurative keratitis - John P Whitcher (Community Eye Health Journal, 2009)
The aim of this article is to review both bacterial and fungal keratitis, with an emphasis on identification and management at the primary, secondary, and tertiary levels. Guidelines for referral will be suggested.